Faktor-faktor yang Mempengaruhi Financial Distress pada Pemerintahan Provinsi di Sumatera - Anjani, Regyna Rachmadilla; Maria, Maria; Armaini, Rossy (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to examine the factors that influence financial distress in provincial governments in Sumatra in terms of the degree of decentralization, budgetary solvency ratio and growth ratio. The testing method uses a quantitative approach with secondary data on LHP obtained via the BPK RI website in 2018-2022. The population used includes all provinces on the island of Sumatra, totaling 10 provinces for the 2018-2022 fiscal year and each member of the population was taken as a sample using a saturated sampling technique, so that the observation units in this research were 50 samples. This research uses Eviews to analyze the data. The results of the research show that simultaneously there is a significant influence between the variables degree of decentralization, budgetary solvency ratio and growth ratio on financial distress in provincial governments in Sumatra, partially the degree of decentralization has a negative and significant influence on financial distress, while the budgetary solvency ratio has a positive and significant influence on financial distress and the growth ratio does not have a significant effect on financial distress in provincial governments in Sumatra during the 2018-2022 period.